Ecosystem approach to health (Ecohealth): Theory and practices in environmental health research in Vietnam - Hung Nguyen-Viet; Tran Thi Tuyet Hanh (Medical Publishing House, 2016)
Together with the economic development, urbanization, population growth and war legacies, Vietnam has been facing with various severe impacts on the environment, ecosystem and human health. Ecosystem approaches to health, or Ecohealth, is an emerging field of transdisciplinary research that brings together public health, environmental health people, veterinarians, ecologists, social scientists, policy makers, local authorities and experts from other fields and community members to explore how ecosystem changes can have adverse impacts on human health and implement practical solutions to address these health challenges. Six principles of this approach include transdisciplinarity, participation, gender and social equity, system-thinking, sustainability and research-to-action (Charron 2012). This book is one of the important outputs of the regional program “Field Building Leadership Initiative – Advancing Ecohealth in South East Asia - FBLI”, supported by IDRC from 2011 to 2016, which aims to introduce to the readers the Ecohealth approach, its six core principles and application in practices. The opportunities and challenges of applying Ecohealth approach in research in Southeast Asia and in Vietnam are also discussed. The book features 12 modules, which describe and analyse theory and practices of Ecohealth approach in Vietnam and internationally. Module 1 introduces the general concepts of Ecohealth and its core principles. Module 2 to Module 8 present in details the application of each of the six Ecohealth core principles as well as the theory and practices of monitoring and evaluation for Ecohealth research. Module 9 to 12 discuss the practical applications of Ecohealth approach in research and training in Vietnam and in Southeast Asia, in which Module 11 presents different research projects recently implemented in Vietnam applying Ecohealth approach. The content of these modules was based on the international experiences, a book titled Ecohealth Research in Practice - Innovative Applications of an Ecosystem Approach to Health by Dominique F. Charron (2012), as well as research and training experiences of the authors in the Vietnamese context. To our best knowledge, this is the first ever book in Ecohealth published in Vietnamese. Thus, we believe that it will be a useful reference for undergraduate and postgraduate students in the field of Public Health, Environmental Health, Preventive Medicine, Veterinary Medicine, Aquaculture, Animal Sciences, and Social Sciences as well as researchers who are interested in Ecohealth research. The other target groups of this book are practitioners and policy makers who can apply the collective knowledge and transdisciplinary approach into policy and decision making.